The switch : ignite your metabolism with intermittent fasting, protein cycling, and keto - Clement, James W.; Loberg, Kristin (Gallery Books, 2019)
"How can you lose dramatic weight, reverse chronic conditions, and stay healthier longer? Flip the switch on your metabolism with intermittent fasting, protein restriction, and ketosis! Lose weight. Reverse Chronic Conditions. Live Healthier Longer. Within each of us is an ancient mechanism that eliminates toxic materials, initiates fat burning, and protects cells against stress. It's called autophagy, and when it's turned on, the complex operation can not only slow down the aging process, but can optimize biological function as a whole, helping to stave off all manner of disease-from diabetes to dementia-and affording us the healthy lifespan we never thought possible. So how can we activate this switch through diet? How frequently should we fast and for how long? Must we abstain from all foods or just specific macronutrients? What's the sweet spot between intermittent fasting, protein restriction, and ketogenic eating? Backed by a wealth of data, and with a practical program anyone can follow for lasting results, The Switch not only decodes the science of autophagy, but also teaches you how to control it and benefit from its profound impact"--